Réflexions sur l’histoire de l’exposition et de la restauration des effigies de culte anciennes au Cambodge - Sophie Biard (Moussons, 2017)
Ancient statues from angkorian and pre angkorian eras in Cambodia have a long story since they were excavated, or found in modern Wat. We focus here on sandstone statues in the round. These statues had to be restored, to be moved into museums in order to be protected against degradation and looting —forming the collections we know nowadays. But did they had to? Archaeology, museums and science of conservation were brought in Cambodia by the French protectorate, established in 1863. But the meaning that French curators give to these archaeological artefacts is different from the meaning the deeply religious Cambodian society traditionally gave them. And with this difference of meaning comes the difference in conservation treatments both society practiced on these statues. How these practices evolved through time, linked to the different historical events and political contexts Cambodia went through? Which place is allowed to popular worship in museums nowadays?